Analisis Sistem Pengendalian Internal Siklus Penjualan dan Penerima Kas Terhadap Pengendalian Piutang pada Koperasi Rukun Dwijo Tegal - Yusnaldi Yusnaldi; Husen Husen (Universitas Mohammad Husni Thamrin, 2020)
This research aims to update the analysis of the Internal control system of the sales cycle and the recipient of the cash against the control of accounts receivable On Cooperative Rukun Dwijo Tegal, which is very important for the progress of the cooperative. Cash is the object that is easily perverted for avoiding abuses then required the existence of an internal control system. This study uses qualitative methods, qualitative data is data in the form of words, schemes, drawings. The methods used in data retrieval is to interview, interview with Chief operations, data analysis and compare of the theory with the results of the data obtained. Examples of data taken among others: organizational structure, job description, internal policies, documentation, and internal control system flowchart sales cycle and the receipt of cash. Research results show that the division of tasks / responsibilities that are essential in the smooth running of the cooperative Rukun Dwijo Tegal. The sales system in cooperative Rukun Dwijo Tegal using cash sales system. The information is carried out by a cooperative Rukun Dwijo Tegal in record-keeping is already using the computer so that the resulting information is accurate and likely to occur in human error.Keywords: Internal control, sales, Cash Receipt and control of accounts receivable.